Avaliação da efetividade da vinculação de 12% da receita líquida de impostos e transferências para gastos com saúde - Mesquita, Luiz Jarbas de (2012)
In Brazil , public health is a matter of considerable criticism by the public and agencies press, and that those responsible are complaining about the lack of funding for the sector . One attempt to address this problem came with the binding of 12 % of Net Revenue and Taxation Transfers - RLIT for health spending within the states and the Federal District , the Constitutional Amendment No. 29 . This study aims to assess the effectiveness of this policy public and respond if the fulfillment of this binding corresponds to improvements in financial health indices . The relevance is defined by the Federal Constitution states when that " health is a right and duty of the State ." The research , documentary - type quantitative , was performed with the application of statistical methods on data from health spending six states selected , for the period 2001-2009 , and on the health indicators selected for research . The sources are publications of official bodies in the Internet, based on the collection, the data were treated statistically using the tools for that of SPSS , acronym of Statistical Package for the Social Sciences and Microsoft Excel , making comparisons between members of the Federation selected from the standpoint of health spending and looking establish correlations between these costs and the development of health indices , in order to realize the impacts of the Constitutional Amendment on improving or not the health of the population . the Results show that in large part, it can be considered good degree of compliance requirement and that despite an improvement in health indices of the population , this should not be credited only to the application of the law, demonstrating the importance of quality concern spending . At the end , we suggest that further research can answer questions arising in During the data analysis.